2013
DOI: 10.1073/pnas.1303395110
|View full text |Cite
|
Sign up to set email alerts
|

Host and viral features of human dengue cases shape the population of infected and infectious Aedes aegypti mosquitoes

Abstract: Dengue is the most prevalent arboviral disease of humans. The host and virus variables associated with dengue virus (DENV) transmission from symptomatic dengue cases (n = 208) to Aedes aegypti mosquitoes during 407 independent exposure events was defined. The 50% mosquito infectious dose for each of DENV-1-4 ranged from 6.29 to 7.52 log10 RNA copies/mL of plasma. Increasing day of illness, declining viremia, and rising antibody titers were independently associated with reduced risk of DENV transmission. High e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
280
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(312 citation statements)
references
References 27 publications
12
280
2
1
Order By: Relevance
“…For dengue, infectiousness often lasts longer than fever. In experimental feeding studies, infection of mosquitoes was documented up to 2 days before [37] and 2 days after [38] the period of fever, which typically lasts between 2 and 7 days [32]. In a more recent study [39], at a given viremia level, dengue virus infected people with no detectable symptoms or whose symptoms had not yet begun were more infectious to mosquitoes than people who were bitten when they were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…For dengue, infectiousness often lasts longer than fever. In experimental feeding studies, infection of mosquitoes was documented up to 2 days before [37] and 2 days after [38] the period of fever, which typically lasts between 2 and 7 days [32]. In a more recent study [39], at a given viremia level, dengue virus infected people with no detectable symptoms or whose symptoms had not yet begun were more infectious to mosquitoes than people who were bitten when they were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…With DENV, variation occurs in both interspecific and intraspecific serotype-specific ID 50 estimates. For example, the ID 50 for DENV-1 and DENV-2 was lower than for DENV-3 and DENV-4 in one study in Vietnam [36], and field populations of A. aegypti demonstrated lower vector competence for the American genotype of DENV-2 than the Southeast Asian genotype [37]. It has been shown that people with asymptomatic and presymptomatic DENV infections had an approximately 100-fold lower ID 50 and resulted in larger viral loads in infected mosquitoes, which was interpreted as increased transmission potential [38].…”
Section: Vector Competencementioning
confidence: 99%
“…Figure 3 provides another example of a direct mapping from within-human pathogen load data to transmission for dengue infections. For each of the four dengue serotypes, the association between viraemia in dengue patients and the infectiousness of these patients to mosquitoes is shown ( figure 3; [46]). In acute infections, such as dengue, pathogen levels do not reach a defined steady state at which pathogen levels are more or less constant for an extended period.…”
Section: Host Infectiousnessmentioning
confidence: 99%